Experimental Evaluation of Compound System Calls in the Linux Kernel - Vicente, Elder; Matias, Rivalino; Borges, Lucio; Macêdo, Autran (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2011: Anais do I Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2011)
The overhead caused by system calls in many applications has motivated research works focusing on reducing their execution costs. In this work we implement three types of compound system calls, which are evaluated experimentally by taking into account their execution time in systems with one up to eight cores. We also investigate the system calls running in both physical and virtual machines. All proposed compound system calls present performance gains when compared to their conventional counterparts. The results indicate reduction in the execution time up to 58 percent. The dataset obtained through controlled experiments is analyzed using ANOVA and Tukey tests. We also verify that the highest improvements occur in the non-virtualized environment.